Peran Program Pelayanan Rehabilitasi Sosial Anak Berhadapan Hukum (ABH) - Nazira, Faizzatun; Nawangsari, Ertien Rining (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2022)
This study aims to determine how the social rehabilitation service program for children with the law. Using role theory by Biddle and Thomas, this research uses qualitative methods with data collection techniques through interviews, documentation, and observation. focuses on Expectations, Norms, Performance, Evaluation, and Sanctions. The result is that the Marsudi Putra Technical Implementation Unit Surabaya is used as a place of service for the protection of minors who commit criminal acts, with the existence of a rehabilitation center they will get protection rights, the rehabilitation process is given to all clients, sanctions from the Marsudi Putra Technical Implementation Unit can be given to staff who have problems with respect to existing guidelines. The rehabilitation program services provided by the Marsudi Putra Technical Implementation Unit are expected to provide lessons for minors who commit crimes so that they have a deterrent effect and do not make the same mistakes.